Customer's satisfaction on counter services of the Road Transport Department in Keningau, Sabah / Christopher Wong @ Md Redzuan Abdullah - Abdullah, Christopher Wong @ Md Redzuan (2013)
This study is about measuring customer satisfaction on counter services that are provided at the Road and Transport Department in Keningau branch office. The objectives of this study are: (i) To determine the level of customer satisfaction for counter services in RTD Keningau Branch; (ii) To determine the level of customer satisfaction for counter services quality in RTD Keningau Branch; (iii) To determine the level of customer satisfaction for employee performance at the counter in RTD Keningau Branch; (iv) To determine the level of customer satisfaction for office facilities in RTD Keningau Branch; and (v) To determine the relationship between counter service quality, employee performance at the counter, and office facilities with customer satisfaction. This study undertakes a quantitative and descriptive approach using survey as the main method to gather information through self administered questionnaire. This study involves 150 customers who patronize RTD counter services at Keningau branch. The study found that customer satisfaction for the services at the counter of RTD Keningau was low particularly for office facilities. It was also found that there are significant relationships between counter service quality, employees' performance at the counter and office facilities with customer satisfaction but the relationship is weak. It is recommended that for future research, more branches are included in the study so that comparison of service quality and satisfaction for service is enabled.